Polyphenol-rich extracts enhance growth, immune function, and antioxidant defense in juvenile rainbow trout (Oncorhynchus mykiss) - Aghil Mansoori; Hamid Allaf Noveirian; Seyed Hossein Hoseinifar; Mirmasoud Sajjadi; Ghasem Ashouri; Ghasem Ashouri; Roberta Imperatore; Marina Paolucci (Frontiers in Nutrition)
IntroductionThe present study was conducted to investigate the effects of PMIX, a polyphenol-rich extract mixture from chestnut wood and olive, on growth performance, hematological parameters, immunity in serum and skin mucus, hepatic antioxidant enzymes, and intestinal cytokine expression in rainbow trout (Oncorhynchus mykiss).MethodsFour experimental diets containing 0 g PMIX kg−1 diet (control, C), 0.5 g PMIX kg−1 diet (P0.5), 1 g PMIX kg−1 diet (P1), and 2 g PMIX kg−1 diet (P2) were fed to rainbow trout in an eight-week feeding trial. Triplicate groups of fish received each treatment. Growth performance, feed conversion ratio, protein efficiency, hepatosomatic and viscerosomatic indices, hematological parameters, immunity markers, hepatic antioxidant enzyme activities, and intestinal cytokine expression were determined.ResultsPMIX supplementation significantly improved feed conversion ratios, while groups P0.5 and P1 evidenced an increase in growth performance along with protein efficiency ratios. It also showed decreased hepatosomatic and viscerosomatic indices in the P1 group. Except for higher percentages of monocytes in P0.5 and P1, most hematological parameters of the fish did not differ from that of the control. Serum lysozyme and respiratory burst activities were heightened in all PMIX-treated groups, and the skin mucus lysozyme activity was enhanced in P1. The blood phagocytic activity and phagocytic index, serum immunoglobulin, total protein, and bactericidal activity against A. hydrophila did not change. Hepatic superoxide dismutase activity significantly increased in P1 and P2, even though catalase activity did not change. Intestinal interleukin-6 expression was upregulated in all PMIX-treated groups, while tumor necrosis factor-alpha and interleukin-1 beta were upregulated in P1, P2, and P0.5 respectively.DiscussionThe present results evidence that dietary polyphenols from chestnut wood and olive extracts enhance growth performance, antioxidant capacity, and several immunological parameters in the blood, skin mucus, and intestine of rainbow trout. A suitable supplementation level was 1 g PMIX kg−1 diet to separate these improvements.